Enhancing physics experiment skills using smartphone sensors for teachers in sorong regency - Endra Putra Raharja; Intan Java Turis Repmi Tamsih; Mukhlas Triono; Edi Sutomo; Kristin Seru Matonda; Supriyatna Supriyatna (Universitas Muhammadiyah Malang, 2025)
This community service program designed to enhance physics experimental skills using smartphone sensors for high school teacher aims to introduce and train teachers in utilizing simple yet effective technology in physics education. By using smartphone sensors, the goal is to enable teachers to conduct experiments that are not only captivating but also easily accessible and relevant to daily life, thus boosting students’ comprehension and interest. The program was conducted in two phases: first, a training session for teachers, followed by school visit with MGMP team to provide hands-on support, address any challenges teachers may encounter, and observe the implementation of the method. Furthermore, the effectiveness of the program was evaluated based on the results from both pre-assessment and post-assessment conducted on 20 teachers from MGMP group. The assessment results showed increases in understanding and preparing technology, collecting data, and analyzing and evaluating data. Despite several challenges such as limited access to compatible devices and varying levels of understanding regarding the concept, the training was overall successfully improved teachers’ skills in applying the technology for physics experiment.